Identifying Factors Influencing the Efficiency of School Counselors: A Thematic Analysis Study - Dariush Azimi; Hossein Ghamari Givi; Ali Rezaeisharif; Ali Sheykholeslami (Journal of Qualitative Research in Health Sciences)
Background: School counselors are expected to induce changes in schools and to help improve and promote students’ academic, personal/social, and professional development. Accordingly, this study aimed to identify the factors underlying the efficiency of school counselors.Methods: This qualitative study was conducted using a descriptive and exploratory design. Data were collected through semi-structured exploratory interviews and analyzed using thematic analysis. The participants in the study were 13 school counseling professors and experts with research and academic experiences in school counseling. The participants were selected using purposive non-probability (judgmental) sampling and sampling continued until data saturation.Results: The findings showed that factors underlying the efficiency of school counselors included psychological skills (communication and interaction skills, trust-building and persuasion skills, motivational skills, and cognitive skills), technical skills (learning and teaching skills, problem-finding and problem-solving skills, knowledge skills, and research skills), personality traits (responsibility, adherence to human and moral values, initiative, ideation and creativity, effort and patience, risk-taking spirit, and adaptability), and management skills (planning and time management, monitoring the surrounding environment, and decision-making).Conclusion: Addressing the factors contributing to school counselors’ efficiency helps improve their professional competencies and leads to the effectiveness of counseling services offered in schools. Moreover, taking into account these factors can contribute to recruiting more qualified counselors in the educational system.